Psychological Distress in Healthcare Workers between the First and Second COVID-19 Waves: The Role of Personality Traits, Attachment Style, and Metacognitive Functioning as Protective and Vulnerability Factors - Loredana Cena (MDPI AG, 2021)
The COVID-19 pandemic has impacted the mental health of healthcare workers (HCWs) since its outbreak, but little attention has been paid to person-level vulnerability and protective factors. This study aims to determine the prevalence of both general and pandemic-related psychological distress among HCWs between the first and second COVID-19 waves in Italy and analyze associations between psychological distress and personality traits, attachment style, and metacognitive functioning. Between June and October 2020, 235 Italian HCWs completed questionnaires concerning psychological stress, personality traits, attachment style, and metacognitive functioning; 26.5% of respondents presented with moderate to extremely severe levels of general psychological distress and 13.8% with moderate to extremely severe levels of pandemic-related psychological distress. After controlling for demographic and occupational variables, significant associations emerged among high emotional stability as a personality trait and both general (aOR: 0.58, 95% CI: 0.41–0.79) and pandemic-related psychological stress (aOR: 0.62, 95% CI: 0.41–0.90). Additionally, higher scores regarding one’s ability to understand others’ emotional states were associated with lower odds of developing psychological distress (aOR: 0.78, 95% CI: 0.63–0.93). Lastly, when comparing those with fearful attachment styles to those with secure attachments, the aOR for psychological distress was 4.73 (95% CI: 1.45–17.04). These results highlight the importance of conducting baseline assessments of HCWs’ person-level factors and providing regular screenings of psychological distress.